A Reduction in Selenoprotein S Amplifies the Inflammatory Profile of Fast-Twitch Skeletal Muscle in the mdx Dystrophic Mouse - Craig Robert Wright; Giselle Larissa Allsopp; Alex Bernard Addinsall; Natasha Lee McRae; Sofianos Andrikopoulos; Nicole Stupka (Mediators of Inflammation)
Excessive inflammation is a hallmark of muscle myopathies, including Duchenne muscular dystrophy (DMD). There is interest in characterising novel genes that regulate inflammation due to their potential to modify disease progression. Gene polymorphisms in Selenoprotein S (Seps1) are associated with elevated proinflammatory cytokines, and in vitro SEPS1 is protective against inflammatory stress. Given that SEPS1 is highly expressed in skeletal muscle, we investigated whether the genetic reduction of Seps1 exacerbated inflammation in the mdx mouse. F1 male mdx mice with a heterozygous Seps1 deletion (mdx:Seps1−/+) were generated. The mdx:Seps1−/+ mice had a 50% reduction in SEPS1 protein expression in hindlimb muscles. In the extensor digitorum longus (EDL) muscles, mRNA expression of monocyte chemoattractant protein 1 (Mcp-1) (P=0.034), macrophage marker F4/80 (P=0.030), and transforming growth factor-β1 (Tgf-β1) (P=0.056) were increased in mdx:Seps1−/+ mice. This was associated with a reduction in muscle fibre size; however, ex vivo EDL muscle strength and endurance were unaltered. In dystrophic slow twitch soleus muscles, SEPS1 reduction had no effect on the inflammatory profile nor function. In conclusion, the genetic reduction of Seps1 appears to specifically exacerbate the inflammatory profile of fast-twitch muscle fibres, which are typically more vulnerable to degeneration in dystrophy.